Quality of biomaterial during transplantation of embryos (Experimental biology, 2015)
To hired the results of washing of embryos, study of their stage of development are driven, quality description ofembryos with the purpose of determination of fitness for transplantation in ОХ "Irtish"
Keywords: Biotechnology; transplantation; donor; recipient; ovulation; synchronization; moryla; blastocyst